Does Corporate Social Responsibility Improve Community Satisfaction? - Rahma Yuliani; Zaki Mubarak; Arifah Arifah (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2023)
Corporate Social Responsibility is a form of corporate responsibility to stakeholders. PT. Pertamina Patra Niaga Fuel Terminal Tarakan developed a mangrove conservation ecotourism program to avoid degradation in the area by involving the surrounding community. This study aims to find out whether CSR programs improve community satisfaction. The research uses quantitative and qualitative approaches. The analysis used the Community satisfaction index (CSI) with 12 question indicators. The research sample comprised 30 community respondents in the Tanjung Batu area, Mamburungan Village, Tarakan City District. The results showed that the CSI value is 3.25, which after conversion got a value of 81.25, was in the range of 62.51-81.25 in the